Students' perceptions on auditors' liability. - Cheah, Jeremy Soo Ann. (2008)
A survey was conducted on Nanyang Technological University (NTU) first and final year accountancy students. The survey on the first year students found that most students are aware of the rising litigation problem. However, an expectation gap does exist in their understanding of the purpose of auditing. The survey on the final year students shows that most students think that the litigation problem is not as serious in Singapore as compared to US.